Developing and validating utility parameters to establish patient-reported outcome-based perioperative symptom management in patients undergoing prostatectomy: a multicentre, prospective, observational cohort study protocol - Jie Li; Jianguo Gao; Ting Chen; Fusheng Peng; Tengfei Gu; Baiye Jin (BMJ Open, 2023)
Introduction Symptom monitoring and alerting based on patient-reported outcomes have proven valuable in a postoperative setting. However, the parameters of the implemented patient-centred symptom management system for patients with prostate cancer (PC) remain unclear. This study aims to develop a perioperative symptom scale (PSS) to monitor symptoms, determine the appropriate timing for symptom assessment and establish intervention criteria for physicians.Methods and analysis We will prospectively recruit 387 patients undergoing PC surgery in 3 hospitals. The Chinese version of the MD Anderson Symptom Inventory (MDASI) will be used for longitudinal symptom data collection, presurgery and 1, 2, 3, 5, 7, 14, 21, 28, 42 and 90 days post surgery. A PSS will be generated when symptoms change significantly over time. A linear mixed model will be used to determine appropriate follow-up time points. The functional status determined by MDASI interference can then be used to establish alarm thresholds.Ethics and dissemination This study was approved by the Lishui Municipal Central Hospital Ethics Committee on 13 April 2022 (No. LSMCHEC-2022-54) and the Ethics Committee of Huzhou Central Hospital on 5 July 2023 (No. HZCHEC-202306017-01), the Ethics Committee of the First Affiliated Hospital of Huzhou Normal College on 20 June 2023 (No. HZYYEC-2023KYLL055). The latest protocol used in this study was V.2.0, dated on 25 February 2023. Before publication in a peer-reviewed journal, our findings will be presented and discussed at relevant medical conferences.Trial registration number ChiCTR2200059110.